PELAKSANAAN DISPENSASI NIKAH DI BAWAH UMUR DI DESA KULIM JAYA KECAMATAN LUBUK BATU JAYA KABUPATEN INDRAGIRI HULU MENURUT UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Safari, Zui Zui Anita; Hanifah, Mardalena; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Underage marriage is a marriage that is performed by someone who has not met the minimum age limit for marriage . Underage marriage actually be done with specific reasons and must be accompanied by a decree of the Court of Religion according to the contents of Article 7 paragraph ( 2 ) of Law No. 1 of 1974 About Marriage ( hereinafter called the Marriage Act ) . In fact, in the village of Kulim Jaya there are still underage marriage that is not accompanied by a decree granting a dispensation marriage of Islamic Court . The purpose of this thesis research is to determine how the implementation of the dispensation of marriage in the village Kulim Lubuk Batu Jaya Jaya District of Indragiri Hulu , and to know the reason KUA Lubuk Batu Jaya remained married couples under age without a dispensation giving marriage of Religious Court and to know the reasons actors marriage minors do not follow the trial court granting the dispensation of Religion .The method used is Observation Research with juridical sociological approach , sedangkat nature of this thesis research is descriptive . The way research is by way of surveys and structured interviews . Results of the study found is still the presence of underage marriage in Kulim Jaya village which is not accompanied by a decree granting marriage dispensassi of Religious Court . KUA Lubuk Batu Jaya remained married couples under age without a court order as a state religion pregnant outside marriage and economic circumstances are not allowed to attend the session in the Religious . Performers underage marriage did not follow the trial in court to obtain a dispensation Religious marriage by reason of distances , complicated procedures and a long time . Suggestions author , the first expected to KUA Lubuk Batu Jaya in order not to marry underage partner without marriage dispensation decree of Islamic Court . Both the KUA Lubuk Batu Jaya to be more prudent in giving the decision to marry couples under age , and the third to parents whose children will marry underage dispensassi it has obtained a marriage in the Religious .Keywords : Dispensation of Marriage , Marriage Law , Kulim Desa Jaya Indragiri Hulu